Strategi Manajemen dalam Pengembangan Kompetensi Pegawai negeri Sipil di Pemerintahan Aceh - Avrini, Inda (Puslatbang KHAN, 2023)
Competency development is a requirement for Civil Servants (PNS) to encounter work challenges and demands in order to provide excellent services for the public. The Aceh Government's Employee Professionalism Index (IPP) of 52% shows that overall employee competency is still at a very low level. Therefore, strategic management is essentially required so that competency development for the civil servants can be implemented within existing constraints and limitations. Strategic management is a design or approach applied by an organization to achieve its goals and vision, in this case is to accomplish competency development programs. Regulations for civil servant competency development have been mandated in the relevant regulations and legislation, however the competency development program has yet been implemented optimally. Qualitative approach with descriptive methods is used in this paper, data presentation is carried out by collecting and compiling data, and tabulating the results obtained from the Employee Professionalism Index (IPP) in several agencies in the Aceh government. The results show that there are several factors in implementing the competency development program for civil servants in the Aceh Government and can be addressed by several alternative policies.